Characteristics and Activities of Women with Socio-Economic Prone in the Pattingaloang Baru Village, Ujung Tanah District, Makassar City - Ibnu Hajar; Andi Agustang; Arlin Adam (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The role of women in the family is very influential in welfare as the smallest unit in society. Women must play an active role in changing their own circumstances, especially women who are vulnerable to socioeconomic conditions, the position of women in a modern perspective no longer sees women as mere objects, but rather their position as subjects who play a role in economic life, therefore this study aims to determine their activities and characteristics. Socioeconomic vulnerable women. This research is a form of social research that uses a qualitative descriptive format that aims to describe, summarize various conditions, as situations or various social reality phenomena that exist in society which are the object of research, and attempt to draw that reality to the surface as a characteristic, character, and nature. , sign model, or a description of certain conditions, situations, or phenomena. Women who are socially and economically vulnerable in Darmaguna village are relatively aged 20-40 years, have the status of widows, have low education and limited skills, and have a large number of dependents. In fulfilling physiological, economic, emotional, intellectual, and religious needs, it still shows a very low presentation.